Integrating seasonal variation into conservation planning can provide extra benefits: A case study in the Tana River Basin, Kenya - Jiacheng HUANG; Sisi YU; Kelvin Babu GITHAIGA; Samwel Maina NJUGUNA; Janet ONYANGO; Xue YAN (Ecological Indicators)
Seasonal variations in climatic conditions induce spatio-seasonal changes of ecological indicators, such as ecosystem services and biodiversity. However, current conservation planning mostly focus on annual or long-term characteristics of ecological indicators, with limited considerations of their seasonal variations. It remains unclear whether integrating seasonal variation into conservation planning can provide extra benefits. This study examines the Tana River Basin, a typical basin significantly affected by seasonal variations, to integrate these variations into ecological network construction and assess its benefits for conservation. Results demonstrated that integrating seasonal variation indeed improve protection efficiency. Compared to the annual perspective, considering seasonal stability can increase the soil conservation by 82.79 %, water yield by 14.55 % and net primary productivity by 16.78 %, respectively. Meantime, it enables the adjustments of conservation planning based on the seasonal ecological resistance. For instance, compared to long rainy season, the long dry season decreased ecological corridor areas by 33.87 % and increased barrier points by 428.92 %. Accordingly, ecological sources covering an area of 20,758 km2 within the basin were identified in the upper and lower reaches. Ecological corridors were classified into primary and seasonal (Level I and II) corridors to clarify the different priorities. A number of 52 and 22 of hierarchical ecological pinch points and hierarchical barrier points were also identified, respectively. Finally, a “two zones, two axes, five nodes, and multiple corridors” ecological conservation pattern and targeted suggestions for different seasons were proposed. These results provide prioritization information for ecological conservation, supporting for sustainable development of the Tana River Basin.